PENGARUH PROPORSI KOMITE AUDIT INDEPENDEN, AUDIT TENURE DAN PROPORSI KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Wahyudianto Matanari (Fakultas Ekonomi Universitas Advent Indonesia, 2018)
The purpose of this study was to determine whether there was a significant effect on the proportion of independent audit committees, audit tenure and the proportion of managerial ownership on earnings management partially and simultaneously. The variables studied were variable proportion of independent audit committees, audit tenure and the proportion of managerial ownership as independent variables and earnings management (discretionary accruals as the measurement) as the dependent variable. This study used secondary data from banking companies listed in Indonesia Stock Exchange. The sample were obtained using purposive sampling method with a sample of banking companies with a three year period. The data processed using SPSS. The results of this study shown that the proportion of independent audit committees, audit tenure and the proportion of managerial ownership partially and simultaneously no significant effect on earnings management. The proportion of independent audit committees and the proportion of managerial ownership had a negative influence on the direction of earnings management, while audit tenure had a positive influence direction. The negative influence shown when the higher level of the proportion of independent audit committees and the proportion of managerial ownership it will decrease the earnings management. The positive influence shown when audit tenure taken longer it will increase earnings management.